Pretending to be the Good Guy. How to Increase ODA Inflows while Abusing Human Rights - Maya Schmaljohann (University of Heidelberg, Department of Economics, 2013)
I investigate the effect of ratification of different human rights treaties adopted by the United Nations General Assembly on Official Development Assistance (ODA) by donors of the OECD Development Assistance Committee (DAC). On average the ratification of an additional human rights treaty increases total ODA by 6% (around 33.5 million USD) and the ratification of one of the two most important treaties, on torture and civil and political rights, increases total ODA by up to 19% (around 97million USD). Additionally I show that countries with low human rights compliance can use treaty ratification as a substitute for actual improvements in their protection of human rights. While ratification of the two most important treaties does not increase ODA for countries with low levels of respect for human rights, it increases aid commitments for those countries with the lowest respect for human rights by almost 42%. This pattern does not significantly differ between the Nordic donors and the five most important DAC donors. The results become stronger when taking possible endogeneity of treaty ratification into account.
urn:nbn:de:bsz:16-heidok-155115
Keywords: 330; aid allocation; human rights; UN treaties